Perbedaan Pengaruh Pola Pikir Siswa-Siswi SMP Negeri 37 Jakarta Dalam Mengatasi Masalah Bullying Untuk Persiapan Masaa Depan Indonesia - Sinaga, Demak Angelina; Rasyid, Emir Abdur; Sabrina, Aisyah Fatma; Gultom, Chelsea Merrysha Khana; Subakdi, Subakdi; Mulyadi, Mulyadi; Manalu, Ronald; Basri, Hasan (Jurnal Pengabdian Kepada Masyarakat Kalam, 2024)
Bullying is a form of violent behavior with the power to hurt someone verbally, physically or psychologically, intentionally and repeatedly. Bullying is also a social problem that often occurs anywhere and can damage a person's mental health and future, especially in educational environments. This counseling aims to increase the awareness of students at SMP Negeri 37 Jakarta about the dangers of bullying and its impact on life, where many students still think that bullying is not a serious problem and many of them do not understand what aspects/actions are included in it. bullying. Therefore, the material we present includes the meaning of bullying, its types, its psychological impact, as well as steps to prevent and handle it. The method we use is a quantitative method using a survey approach, where data is collected through questionnaires to measure students' understanding of bullying. The results of this activity show an increase in students' understanding of bullying and the importance of prevention. Although there were challenges in terms of active participation from some students, this activity succeeded in achieving its main goal, namely increasing students' awareness and understanding of bullying